Persepsi Kerja Alumni Ilmu Perpustakaan UIN Raden Fatah Dalam Perspektif Adaptasi Karir dan Sistem Ekologi - Rusmiatiningsih, Rusmiatiningsih; Rohmaniyah; Indah Solehati; Clara Milensen; Intan Cahya Ningtyas (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the level of work perception among alumni of the Library Science Study Program at UIN Raden Fatah Palembang and the influence of career adaptability and system ecology on it. This study aims to determining the level of confidence in the alumni's abilities through the influence of career adaptation and the social environment. The research method used in this study is a quantitative approach with a questionnaire distributed to 100 alumni. The data obtained was analyzed using descriptive statistical analysis and PLS-SEM techniques and enriched through structured interviews. The results show that alumni have a very high level of self-perceived employability (grand mean 4.24), with the highest indicator being the ability to learn and develop new skills (mean 4.50) and the lowest being involvement in professional networks (mean 3.98). In addition, career adaptability and system ecology were found to have a positive and significant effect on improving alumni's perceptions of their ability to obtain, develop, and maintain a career. At the same time, the results of the study also revealed that the skills needed by alumni, whether working as librarians, non-librarians, or those who are not yet working, include networking, communication, library digitization, and the use of AI tools.